RAD51 135G–C modifies breast cancer risk among BRCA2 mutation carriers: results from a combined analysis of 19 studies - Antoniou, Antonis C.; Sinilnikova, Olga M.; Simard, Jacques; Léoné, Mélanie; Dumont, Martine; Neuhausen, Susan L.; Struewing, Jeffery P.; Stoppa-Lyonnet, Dominique; Barjhoux, Laure; Hughes, David J.; Coupier, Isabelle; Belotti, Muriel; et al. (American journal of human genetics, 2007)
RAD51 is an important component of double-stranded DNA-repair mechanisms that interacts with both BRCA1 and BRCA2. A single-nucleotide polymorphism (SNP) in the 5’ untranslated region (UTR) of RAD51, 135G–\textgreaterC, has been suggested as a possible modifier of breast cancer risk in BRCA1 and BRCA2 mutation carriers. We pooled genotype data for 8,512 female mutation carriers from 19 studies for the RAD51 135G–\textgreaterC SNP. We found evidence of an increased breast cancer risk in CC homozygotes (hazard ratio [HR] 1.92 [95% confidence interval CI 1.25-2.94) but not in heterozygotes (HR 0.95 [95% CI 0.83-1.07]; P=.002, by heterogeneity test with 2 degrees of freedom [df]). When BRCA1 and BRCA2 mutation carriers were analyzed separately, the increased risk was statistically significant only among BRCA2 mutation carriers, in whom we observed HRs of 1.17 (95% CI 0.91-1.51) among heterozygotes and 3.18 (95% CI 1.39-7.27) among rare homozygotes (P=.0007, by heterogeneity test with 2 df). In addition, we determined that the 135G–\textgreaterC variant affects RAD51 splicing within the 5’ UTR. Thus, 135G–\textgreaterC may modify the risk of breast cancer in BRCA2 mutation carriers by altering the expression of RAD51. RAD51 is the first gene to be reliably identified as a modifier of risk among BRCA1/2 mutation carriers.